2017
DOI: 10.19027/jai.16.2.223-233
|View full text |Cite
|
Sign up to set email alerts
|

The population growth and the nutritional status of Moina macrocopa feed with rice bran and cassava bran suspensions

Abstract: Moina macrocopa culture density can be improved by optimizing the fecundity, and somatic growth through the regulation of quality and quantity of feed. The purpose of this study were to determined how to use effectively the rice bran and cassava bran Manihot utilisima suspension on Moina, based on population, neonates production, adult percentage, biomass, metabolisme and nutritional state. In this study, Moina were cultured for eighth days using four concentrations of rice bran suspension and three concentrat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 25 publications
1
9
0
Order By: Relevance
“…Many authors cited that the low concentration of yeast did not influence water quality [ 27 , 32 , 33 ]. Rice bran was successfully used as feed for copepods, daphnia, artemia, and moina cultures [ 35 , 41 , 42 ]. Amian et al [ 36 ] cited that the diversity and abundance of Copepoda, Rotifera, and Cladocera were enhanced when using rice bran in fishponds during the rearing of tilapia.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Many authors cited that the low concentration of yeast did not influence water quality [ 27 , 32 , 33 ]. Rice bran was successfully used as feed for copepods, daphnia, artemia, and moina cultures [ 35 , 41 , 42 ]. Amian et al [ 36 ] cited that the diversity and abundance of Copepoda, Rotifera, and Cladocera were enhanced when using rice bran in fishponds during the rearing of tilapia.…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, comparing to the fatty acid compositions of copepods fed on soybean, yeast, and corn starch, the fatty acid composition of copepods fed on rice bran resulted in the highest significant MUFA and PUFA, as well as the lowest significant SFA and the lowest SFA/UFA ratio. These findings may be due to the nutritional value of rice bran [ 35 , 41 ]. Bhat et al [ 58 ] cited that commercial grade rice bran contains 50% carbohydrate, 15% protein, 20% fatty acids (linoleic and oleic acids), 5% Vitamin E (tocatrienols, tocopherols, oryzanols, phytosterols), and a low amount of other micronutrients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…as a nutrition source (Shidik et al, 2021). It was reported that the feed's protein and amino acid concentrations directly affected the fecundity and population growth of M. macrocopa (Mubarak et al, 2017). It was also reported that the high fertility and reproductive rate of Cladocera could be obtained when its food source had a high carbon/nitrogen ratio (Khoo et al, 2013).…”
Section: The Growth Of Moina Sp In Different Mediamentioning
confidence: 99%